T‐ and B‐cell responses and previous exposure to hepatitis B virus in 'anti‐HBc alone' patients. Issue 12 (15th June 2015) - Wang, Q.; Sachse, P.; Semmo, M.; Lokhande, M.; Montani, M.; Dufour, J.‐F.; Zoulim, F.; Klenerman, P.; Semmo, N.
Summary A serologic response to hepatitis B virus (HBV) defined as 'anti‐HBc alone' is commonly observed, but its significance remains unclear. This study aimed to define the relationship between 'anti‐HBc alone' serostatus and HBV infection, including HBV‐specific T‐ and B‐cell memory responses. We enrolled 31 'anti‐HBc alone' patients. Total HBV DNA and cccDNA were tested by nested polymerase chain reaction (PCR) analysis in liver samples from 22 'anti‐HBc alone' patients vs controls (chronic or resolved HBV infection), followed by HBsAg/HBcAg immunohistochemical (IHC) staining. IFN‐γ secretion by HBV‐specific T cells was compared in individuals who were 'anti‐HBc alone' (n = 27), resolved HBV (n = 21), chronic HBV (n = 24) and 12 healthy controls using enzyme‐linked immunospot (ELISpot) assays. An HBsAg‐IgG B‐cell ELISpot assay was performed in 'anti‐HBc alone' patients before and after one dose of recombinant HBsAg vaccine. The majority (23/31, 74.2%) of the 'anti‐HBc alone' individuals were co‐infected with HCV. Infrequent intrahepatic total HBV DNA (2/22, 9.1%) and cccDNA (1/22, 4.5%) were detected in biopsies; HBsAg and HBcAg IHC staining was negative. HBV‐specific T‐cell responses were similar between 'anti‐HBc alone' individuals and HBV resolvers. Circulating HBV‐memory B‐cell responses were detected in all 'anti‐HBc alone' individuals, consistent with an HBsAg‐specific memory pool. After one HBV vaccine dose, increased anti‐HBs antibody levels were observed, accompanied by an expansion of HBsAg‐specific memory B cells (P = 0.0226). 'Anti‐HBc alone' individuals showed HBV‐specific T‐cell and memory B‐cell responses typical of previous viral exposure and protective memory, suggesting a resolved infection.